2012
DOI: 10.1007/s12645-012-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of nanoparticles to brain metastases of breast cancer using a cellular Trojan horse

Abstract: As systemic cancer therapies improve and are able to control metastatic disease outside the central nervous system, the brain is increasingly the first site of relapse. The blood–brain barrier (BBB) represents a major challenge to the delivery of therapeutics to the brain. Macrophages originating from circulating monocytes are able to infiltrate brain metastases while the BBB is intact. Here, we show that this ability can be exploited to deliver both diagnostic and therapeutic nanoparticles specifically to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 44 publications
2
117
0
1
Order By: Relevance
“…38 In recent years, it has been shown that leukocytes are effective in carrying drugs and nanoparticles for cancer therapy, 39,40 while leukocyte cell membrane-camouflaged nanoparticles preserve the surface properties of parent leukocytes and provide a platform for biomimetic delivery. 22,[41][42][43] ICAM-1 is a ligand for LFA-1, which is found on vascular endothelium, squamous cell …”
Section: Discussionmentioning
confidence: 99%
“…38 In recent years, it has been shown that leukocytes are effective in carrying drugs and nanoparticles for cancer therapy, 39,40 while leukocyte cell membrane-camouflaged nanoparticles preserve the surface properties of parent leukocytes and provide a platform for biomimetic delivery. 22,[41][42][43] ICAM-1 is a ligand for LFA-1, which is found on vascular endothelium, squamous cell …”
Section: Discussionmentioning
confidence: 99%
“…Near-IR light-induced intracellular release was performed in MDA-MB-231 and SKBR3 (overexpresses HER2) breast cancer cells and compared with release in noncancerous RAW 264.7 macrophage cells. Macrophages were used as the control cells, as they have been shown to be able to phagocytose nanoparticles and deliver them to metastatic tumors where photothermal therapy can be applied (34,35). Future studies would involve macrophages delivering these particles for targeted in vivo drug release.…”
mentioning
confidence: 99%
“…It has also been widely demonstrated that leukocytes were able to efficiently phagocytize NPs by endocytosis (Choi et al, 2012) (Figure 4C), highlighting their advantages over other cells as drug carriers. The ''Cell-NPs'' drug delivery system can be achieved by simply incubation.…”
Section: Internalizationmentioning
confidence: 74%